Food Avoidance and Food Modification Practices of Older Rural Adults: Association With Oral Health Status and Implications for Service Provision - Quandt, Sara A. (Oxford University Press, 2010)
Purpose: Dietary variation is important for health maintenance and disease prevention among older adults. However, oral health deficits impair ability to bite and chew foods. This study examines the association between oral health and foods avoided or modified in a multiethnic rural population of older adults. It considers implications for nutrition and medical service provision to this population. Design and Methods: In-home interviews and oral examinations were conducted with 635 adults in rural North Carolina counties with substantial African American and American Indian populations. Avoidance and modification data were obtained for foods representing different dental challenges and dietary contributions. Data were weighted to census data for ethnicity and sex. Bivariate analyses of oral health measures and foods avoided used chi-square and logistic regression tests. Multivariable analyses used proportional odds or nominal regression models. Results: Whole fruits and raw vegetables were the most commonly avoided foods; substantial proportions of older adults also avoided meats, cooked vegetables, and other foods. Food avoidance was significantly associated with self-rated oral health, periodontal disease, bleeding gums, dry mouth, having dentures, and having fewer anterior and posterior occlusal contacts. Associations persisted when controlling for demographic and socioeconomic status indicators. From 24% to 68% of participants reported modifying specific fruits, vegetables, and meats. Modifying harder foods was related to location of teeth and periodontal disease and softer foods to oral pain and dry mouth. Implications: Food services for older adults should consider their oral health status. Policy changes are needed to provide oral health care in benefits for older adults.